Diseño de un prototipo de turbina eólica de eje vertical para pruebas de laboratorio (2018)
Nowadays, wind energy emerges as an alternative for electric energy generation in zones which are not connected to the National Electric Grid. This project focuses on the design and the aerodynamic study of a small-scale vertical axis wind turbine. In this study, the effect of the Pitch angle in the power coefficient is evaluated. The tests to be carried out in the wind turbine prototype were defined from studies previously carried out by other authors due to the international standard that regulates this kind of equipment (IEC 61400) does not include any kind of aerodynamic tests. The selected tests are based on the comparison of the power coefficient with the tangential speed ratio to analyze the performance of the turbine, they are also based on the analysis of the torque produced along the azimuth, in order to identify the power gain zone and the power loss zone. A preliminary design of the prototype was carried out and the Double Multiple Streamtube Model (DMST) was implemented on it in order to predict the turbine power coefficient. By varying some parameters (chord length, height of the blades, aerodynamic profile) it is posible to guarantee the dimensions for the wind turbine with which the predicted power coefficient is the highest. However, due to limitations of the DMST (solidity ≤ 0.2), it was necessary to design another prototype in order to properly implement the analytical model.